Characteristics and outcomes of initial virologic suppressors during analytic treatment interruption in a therapeutic HIV-1 gag vaccine trial. - Jonathan Z Li; Chanson J Brumme; Michael M Lederman; Zabrina L Brumme; Hongying Wang; John Spritzler; Mary Carrington; Kathleen Medvik; Bruce D Walker; Robert T Schooley; Daniel R Kuritzkes; AIDS Clinical Trials Group A5197 Study Team (PLoS ONE)
Background In the placebo-controlled trial ACTG A5197, a trend favoring viral suppression was seen in the HIV-1-infected subjects who received a recombinant Ad5 HIV-1 gag vaccine. Objective To identify individuals with initial viral suppression (plasma HIV-1 RNA set point <3.0 log(10) copies/ml) during the analytic treatment interruption (ATI) and evaluate the durability and correlates of virologic control and characteristics of HIV sequence evolution. Methods HIV-1 gag and pol RNA were amplified and sequenced from plasma obtained during the ATI. Immune responses were measured by flow cytometric analysis and intracellular cytokine expression assays. Characteristics of those with and without initial viral suppression were compared using the Wilcoxon rank sum and Fisher's exact tests. Results Eleven out of 104 participants (10.6%) were classified as initial virologic suppressors, nine of whom had received the vaccine. Initial virologic suppressors had significantly less CD4+ cell decline by ATI week 16 as compared to non-suppressors (median 7 CD4+ cell gain vs. 247 CD4+ cell loss, P = 0.04). However, of the ten initial virologic suppressors with a pVL at ATI week 49, only three maintained pVL <3.0 log(10) copies/ml. HIV-1 Gag-specific CD4+ interferon-γ responses were not associated with initial virologic suppression and no evidence of vaccine-driven HIV sequence evolution was detected. Participants with initial virologic suppression were found to have a lower percentage of CD4+ CTLA-4+ cells prior to treatment interruption, but a greater proportion of HIV-1 Gag-reactive CD4+ TNF-α+ cells expressing either CTLA-4 or PD-1. Conclusions Among individuals participating in a rAd5 therapeutic HIV-1 gag vaccine trial, initial viral suppression was found in a subset of patients, but this response was not sustained. The association between CTLA-4 and PD-1 expression on CD4+ T cells and virologic outcome warrants further study in trials of other therapeutic vaccines in development. Trial registration ClinicalTrials.gov NCT00080106.